Wolbachia Endosymbionts of Fleas Occur in All Females but Rarely in Males and Do Not Show Evidence of Obligatory Relationships, Fitness Effects, or Sex-Distorting Manipulations - Flatau, Ron; Segoli, Michal; Hawlena, Hadas (Frontiers in Microbiology, 2021)
The widespread temporal and spatial persistence of endosymbionts in arthropod host populations, despite potential conflicts with their hosts and fluctuating environmental conditions, is puzzling. Here we disentangled three main mechanisms that are commonly proposed to explain such persistence, namely, obligatory relationships, in which the host is fully dependent on its endosymbiont, fitness advantages conferred by the endosymbiont, and reproductive manipulation imposed by the endosymbiont. Our model system reflects an extreme case, in which the Wolbachia endosymbiont persists in all female flea hosts but rarely in male ones. We cured fleas of both sexes of Wolbachia but found no indications for either lower reproduction, offspring survival, or a change in the offspring sex-ratio, compared to Wolbacia-infected fleas. These results do not support any of the suggested mechanisms. We highlight future directions to advance our understanding of endosymbiont persistence in fleas, as well as in other model systems, with extreme sex-differences in endosymbiont persistence. Insights from such studies are predicted to shed light on the evolution and ecology of arthropod-endosymbiont interactions in nature.